Cephoids: duality and reference vectors - Diethard Pallaschke; Joachim Rosenmüller (Bielefeld University, Institute of Mathematical Economics (IMW), 2007)
A cephoid is a Minkowski sum of finitely many prisms in Rⁿ. We discuss the concept of duality for cephoids. Also, we show that the reference number uniquely defines a face. Based on these results, we exhibit two graphs on the outer surface of a cephoid. The first one corresponds to a maximal face and its reference system. The second graph describes the generalized tentacles.
urn:nbn:de:hbz:361-11006
Keywords: 330; Convex analysis; Minkowski sum; Polytopes; Cephoids; Duality; Matrizenrechnung; Theorie